Analysis of the goals scored in the 2016 and 2017 CONMEBOL Libertadores Cups - Andrés González-Ramírez; Matías de Pablo (Colégio Brasileiro de Ciências do Esporte, 2021)
ABSTRACT This study aimed to describe regularities in soccer goal-ending sequences in the 2016 and 2017 CONMEBOL Libertadores Cups. Observational methodology was used. The sample comprised 699 attack sequences that ended in goal from 250 games played in 2016 and 2017. An ad hoc observational instrument was designed. Data analysis was performed in three complementary ways: sequential, graph theory, and polar coordinates. Two sequences were highlighted: Pass with the head-Shot-Goal and Rebound-Rebound-Shot-Goal. The foot pass action is the most common prior to a shot. In addition, dribbling and conducting were excitatory and inhibitory actions, respectively, to score a goal. In conclusion, the use of open game was relevant to score goals and different patterns were observed.